Idiopathic Hematuria in a Near-Term Neonate: A Rare Case and its Workup: Hematuria in Neonates - Redwood, Beau; Saw, Chia; Kulasekaran, Karthikeyan (Journal of Pediatric Nephrology, 2022)
Neonatal hematuria is a very rare occurrence and is mostly due to secondary pathology. This case report describes a rare case of a near-term male neonate with gross Hematuria seen immediately after birth. Urine microscopy confirmed hematuria without growth in urine or blood cultures. A full blood count and coagulation profile showed no obvious cause for the Hematuria, and a renal tract ultrasound showed a mobile haematoma in the bladder but no other structural abnormalities. The newborn received an additional dose of intravenous vitamin K and was managed conservatively. The Hematuria resolved on the second day of life without recurrence on his 12-month follow-up, with no clear cause for the presentation. We discuss a rare case of neonatal gross Hematuria, its differential diagnoses, and clinical approach.